Skin graft associated with platelet-rich plasma in correcting extensive injuries resulting from the resection of skin cancer chemically induced in rats - Josiane Morais Pazzini; Stella Habib Moreira; Pedro Cassino; Marjury Maronezi; Michelle Zangirolami; Jorge Luis Alvaréz Gomés; Paulo Henrique Bertolo; Michelle do Carmo Pereira Rocha; Sonia Prince Fiebi; Caroline Kajiura; Filippo Janoni Bernardes; Caio Bustamante; et al. (Acta Cirúrgica Brasileira, 2022)
ABSTRACT Purpose: To evaluate whether using platelet-rich plasma (PRP) in the graft recipient bed after the resection of a neoplasia can influence its recurrence because this product stimulates angiogenesis, mitogenesis and chemotaxis. Methods: A study with 30 rats Wistar (Rattus norvegicus albinus), which were separated into group A (induction of carcinogenesis, PRP in the postoperative period) and group B (induction of carcinogenesis, absence of PRP in the postoperative period), with 15 animals in each. Carcinogenesis was induced on the skin of the animals’ chest by the topical application of 0.5% dimethylbenzantracene (DMBA) diluted in acetone. After surgical resection of the induced neoplasia, PRP was used to stimulate angiogenesis before surgical wound synthesis. Data on the control and experimental groups and macroscopic and microscopic variables were evaluated using analysis of variance and the Tukey’s test (5%). Results: It was possible to determine that the use of PRP is good in reconstructive surgeries, but it is contraindicated in patients during tumor resection, as it can cause changes in the surgical bed, in addition to stimulating recurrences and metastases. Conclusions: PRP may interact with tumour cells that were in the recipient site of the surgical wound during the resection of a neoplasia, and a local recurrence process can be triggered by applying this product.